A rapid assay for the detection of resistance to phosphine in the lesser grain borer, Rhyzopertha dominica (F.) (Coleoptera: Bostrichidae). (March 2021) - Afful, E.; Cato, Aaron; Nayak, Manoj K.; Phillips, Thomas W.
Abstract: Resistance to the fumigant phosphine in stored product insect pests is a global problem. Diagnosis of resistance relies on a bioassay developed by the FAO that involves a mortality assessment after 20-h fumigation of a pest population at a discriminating concentration of gas, followed by a 14-day post fumigation assessment. This bioassay is impractical for monitoring and early detection of phosphine resistance in routine pest management. We utilized the procedure of a commercial resistance detection test kit for rapid detection in field populations of lesser grain borer, Rhyzopertha dominica (F.). We established a knockdown effect of either susceptible or resistant insects by exposing them to a high concentration of phosphine. We assessed the relationship between adult knockdown times and the FAO method for 18 beetle populations utilizing knockdown criteria for a single beetle in a chamber, or for 50% or 100% knockdown times for groups of beetles, exposed to 3000 ppm of phosphine. We also determined the most effective concentrations that would elicit the quickest knockdown while estimating the recovery times from exposure. Results suggest that a KT100 test was better than the KT50 and the KTsingle tests. Based on the responses of susceptible populations, we established that a KT100 of approximately 18 min can be used as a viable knockdown time to distinguish a susceptible from a resistant populations. Higher concentrations of phosphine significantly elicited a quicker recovery in strongly resistant populations compared to susceptible populations. These findings have potential for developing a robust commercial kit for practical phosphine resistance detection in populations of R. dominica by commercial fumigators, and could be incorporated in a resistance management program. Highlights: Rhyzopertha dominica, the lesser grain borer (LGB) is a serious stored grain pest. LGB has evolved resistance to the fumigant phosphine (PH3) in many countries. Laboratory assays to determine PH3 resistance are technical and lengthy. A simple knock-down test for LGBs determined resistance in about an hour.